2021
DOI: 10.48550/arxiv.2110.03093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Converse Sum of Squares Lyapunov Function for Outer Approximation of Minimal Attractor Sets of Nonlinear Systems

Abstract: Many dynamical systems described by nonlinear ODEs are unstable. Their associated solutions do not converge towards an equilibrium point, but rather converge towards some invariant subset of the state space called an attractor set. For a given ODE, in general, the existence, shape and structure of the attractor sets of the ODE are unknown. Fortunately, the sublevel sets of Lyapunov functions can provide bounds on the attractor sets of ODEs. In this paper we propose a new Lyapunov characterization of attractor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…We begin with presenting the infinite dimensional optimization problems for global attractors from [21] and [11].…”
Section: Two Infinite Dimensional Optimization Problems For the Globa...mentioning
confidence: 99%
See 4 more Smart Citations
“…We begin with presenting the infinite dimensional optimization problems for global attractors from [21] and [11].…”
Section: Two Infinite Dimensional Optimization Problems For the Globa...mentioning
confidence: 99%
“…Some approximate the attractor by following trajectories for long but finite time T ∈ [0, ∞) or using set oriented methods as in [5]. Another approach motivated by a relaxation of the notion of Lyapunov functions was given in [11]. There the authors showed that the weaker concept of Lyapunov function they use is still sufficient to envelope the attractor by positively invariant sets while at the same time SOS polynomials can be used.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations